Continuing professional development training needs for primary care doctors in central Uganda - Jane Frances Namatovu; William Buwembo; Janet Nakigudde; Sarah Kiguli; Aloysius G. Mubuuke (AOSIS, 2023)
Background: Continuing professional development (CPD) activities relevant to medical doctors and their patients should be informed by current assessed training needs. The CPD provision is expected to improve the quality of professional practice and ethics. However, the Uganda Medical and Dental Practitioners' Council still receives about 40 reports of malpractice every month. Aim: The study aimed to describe the CPD training needs of doctors working in public primary care facilities in central Uganda. Setting: The district health system of central Uganda comprised 10 General Hospitals (GH) and 37 Health Center IVs (HC IVs) with a staffing norm of six and two doctors, respectively. Methods: This was a cross-sectional survey of 100 doctors working in public primary care facilities using the World Health Organization (WHO) Hennessy-Hicks questionnaire. Descriptive statistics of the importance, current performance, and training need of each skilled activity were calculated. Content analysis was applied to data from the open-ended questions. Results: The response rate was 91%, majority were males, 80 (87.9%) from 7 GHs and 24 HC IVs with an average age of 37.9 years. The domain with the highest CPD training need for the doctors was research and audit, with a mean score (standard deviation [s.d.]) of 1.94 (±1.69), followed by administration 1.58 (±1.61) and clinical tasks 1.28 (±1.29). The clinical tasks domain had the most suggested CPD topics. Conclusion: Research and audit and clinical tasks were identified as important domains for CPD training for doctors in this setting. Contribution: The results give insight into CPD training needs of primary care doctors and guide various CPD providers.